Pengaruh Kualitas Layanan, Kepercayaan, Citra Merek Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Edwin Jeans Indonesia Pada E-Commerce Shopee - Indah Yani, Masriati; Sugiyanto, Sugiyanto (CV. Lafadz Jaya, 2022)
This study aims to determine the effect of service quality, trust, brand image and customer satisfaction on Edwin Jeans Indonesia’s customer loyalty on Shopee e-commerce. The population in this study is people who use Shopee who know Edwin Jeans products in the Jakarta area. The sample in this study was taken using the purposive sampling method as many as 100 respondents. The analytical method used is multiple linear regression analysis to determine the direct and indirect effects between variabels. The results of this study indicate that service quality, trust, brand image and customer satisfaction together have an effect on customer loyalty, service quality has a positive effect on customer loyalty, brand image has a positive effect on customer loyalty, trust and customer satisfaction have no effect on loyalty customer.